2016
DOI: 10.1302/2058-5241.1.000031
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategy for tibial plateau fractures: an update

Abstract: Tibial plateau fractures are complex injuries produced by high- or low-energy trauma. They principally affect young adults or the ‘third age’ population.These fractures usually have associated soft-tissue lesions that will affect their treatment. Sequential (staged) treatment (external fixation followed by definitive osteosynthesis) is recommended in more complex fracture patterns. But one should remember that any type of tibial plateau fracture can present with soft-tissue complications.Typically the Schatzke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
120
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(148 citation statements)
references
References 45 publications
(52 reference statements)
0
120
0
6
Order By: Relevance
“…1,2 For those treated surgically, treatment goals include restoring the articular surface plateau width and mechanical axes while achieving stable fixation to allow for early range of motion. [3][4][5] Despite these strategies, the longterm outcomes remain guarded for tibial plateau fractures: up to 45% of patients may develop posttraumatic arthritis (PTOA). [6][7][8] Traditional treatment options for patients with PTOA include osteotomy, arthrodesis, and total knee arthroplasty (TKA); however, in the majority of patients with end-stage osteoarthritis TKA is the primary option.…”
mentioning
confidence: 99%
“…1,2 For those treated surgically, treatment goals include restoring the articular surface plateau width and mechanical axes while achieving stable fixation to allow for early range of motion. [3][4][5] Despite these strategies, the longterm outcomes remain guarded for tibial plateau fractures: up to 45% of patients may develop posttraumatic arthritis (PTOA). [6][7][8] Traditional treatment options for patients with PTOA include osteotomy, arthrodesis, and total knee arthroplasty (TKA); however, in the majority of patients with end-stage osteoarthritis TKA is the primary option.…”
mentioning
confidence: 99%
“…Because both classifications provide only two-dimensional information of the fracture, a CT-based three-column classification (TCC) would be a good supplement for evaluation [8]. There were already numerous studies which indicated that implementation of the three-column classification (TCC) might improve the surgical outcome of cases of TPFs [9, 10]. This is the first time that the TCC has been used to evaluate the morphological features of tibial plateau fractures in a large sample size of elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the goals of surgical intervention remain the same: restoring the articular congruity, condylar width, and re-establishing limb mechanical alignment. [4][5][6]24 Absolute indications for surgical fixation of tibial plateau fractures include open injuries, compartment syndrome, and injuries with vascular disruption. Relative indications include articular step-off of !…”
Section: Discussionmentioning
confidence: 99%